Revisiting the Etiology of Hemifacial Microsomia / Retomando la etiología de la microsomía hemifacial - Eseonu, Chijioke O.; University of Pittsburgh (2014)
Background: Hemifacial microsomia (HM) is one of the most common congenital facial malformations of newborns worldwide. Despite its prevalence, little is known about its etiology. Features of HM vary among different reports in the literature, affecting ears, mouth, and mandible on one or both sides. Purpose and Methods: We performed a systematic literature review to determine if there is new evidence regarding the pathological origins of HM. During a seven-month period (September 2010-April 2011) an exhaustive electronic database search was constructed. An inclusion criterion, which set the specific parameters of the electronic database search for this review, was implemented using a number of built-in search tools. Results: A total of 1,250 published reports were displayed upon entry of the Boolean phrase “etiology AND hemifacial microsomia.” Of these papers, all of the publications selected for by the inclusion criterion had been published within the last ten years. Concomitantly, with regards to etiological origins, selection of a specific paper had to convey theories or experimental approaches of which had not been published as the main focus of a report more than three times in all with regards to previous documented literature with hemifacial microsomia as its basis. This final inclusion criterion left only eight studies eligible for this review. Reports included the suggestion of an etiologic role of growth hormone deficiency, fluoxetine ingestion, SALL4 expression, BAPX1 expression, and trisomy of chromosome 10. It appears that both genetic and environmental factors play a role in the etiology of HM. These factors include gene mutations, variation in serotonin receptor binding, growth hormone imbalances, and chromosomal abnormalities. Future studies in humans should determine the frequency of etiologic coding mutations in SALL4, BAPX1, and trisomy 10 in HM cases.  Antecedentes: la microsomía hemifacial (MH) es una de las malformaciones faciales congénitas más frecuentes en recién nacidos mundialmente. A pesar de su prevalencia, poco se sabe sobre su etiología. Las características de la MH varían en los diferentes reportes de la literatura; afecta oídos, boca y mandíbula, uni o bilateralmente. Propósito y métodos: se llevó a cabo una revisión sistemática de la literatura para determinar si hay nueva evidencia sobre el origen patológico de la MH. Durante siete meses (septiembre de 2010-abril de 2011) realizamos una búsqueda exhaustiva en bases de datos electrónicas. Un criterio de inclusión que determinó los parámetros específicos de la búsqueda se implementó usando un número de herramientas de búsqueda. Resultados: la búsqueda booleana (“etiology AND hemifacial microsomia”) arrojó un total de 1250 publicaciones. Se seleccionaron reportes publicados en los últimos diez años. Asimismo, con respecto a la etiología, los artículos debían incluir teorías o experimentos que no se hubieran publicado como asunto principal más de tres veces con la MH como base. Este criterio final de inclusión dejó solamente ocho estudios elegibles para la revisión. Los reportes sugieren que una deficiencia en la hormona del crecimiento, ingestión de fluoxetina, expresión de SALL4, expresión de BAPX1 y trisomía del cromosoma 10 como factores etiológicos. Parece que factores genéticos y ambientales cumplen un papel en la etiología de la MH. Estos factores incluyen mutaciones genéticas, variación en la unión del receptor de la serotonina, desbalances de la hormona del crecimiento y anomalías cromosómicas. Estudios futuros en humanos deberían determinar la frecuencia de mutaciones etiológicas en la codificación de SALL4, BAPX1 y trisomía 10 en casos de MH.